2022
DOI: 10.1007/s10484-022-09551-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breathing Rate Variations Linked to Social Exclusion and Emotion Self-assessment

Abstract: The emotional reactions to social exclusion can be associated with physiological responses that could allow researchers to estimate the valence and intensity of the ongoing affective state. In this work, respiratory activity was analysed to verify whether breathing rate variations can be considered as predictive factors of subsequent positive and negative affect after inclusion and exclusion in young women. A standard Cyberball task was implemented and manipulated information was provided to the participants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Experimental research supports a purported mechanism by which organizational stress would be associated with physiological reactivity among police managers. Researchers demonstrate a link between negative social interactions and social exclusion to increases in cardiovascular metrics such as heart rate (HR) and heart rate variability (HRV) (Hidalgo-Muñoz et al, 2022;Liddell & Courtney, 2018). For example, Chen and Drummond (2008) showed that individuals show significant increases in HR, skin conductance and respiration during social evaluative tasks (i.e., singing in front of strangers, listening to audiotapes of themselves), regardless of whether they had a fear of social evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research supports a purported mechanism by which organizational stress would be associated with physiological reactivity among police managers. Researchers demonstrate a link between negative social interactions and social exclusion to increases in cardiovascular metrics such as heart rate (HR) and heart rate variability (HRV) (Hidalgo-Muñoz et al, 2022;Liddell & Courtney, 2018). For example, Chen and Drummond (2008) showed that individuals show significant increases in HR, skin conductance and respiration during social evaluative tasks (i.e., singing in front of strangers, listening to audiotapes of themselves), regardless of whether they had a fear of social evaluation.…”
Section: Introductionmentioning
confidence: 99%